Gold [videorecording (DVD)] - McConaughey, Matthew, 1969-; Ramírez, Édgar, 1977-; Stoll, Corey, 1976-; Howard, Bryce Dallas, 1981- (Anchor Bay, 2017)
Kenny Wells, a prospector desperate for a lucky break, teams up with a similarly eager geologist and sets off on an amazing journey to find gold in the uncharted jungle of Indonesia. Getting the gold was hard but keeping it is even more difficult, sparking an adventure through the most powerful boardrooms of Wall Street.